Readiness to implement electronic medical records based on the california community clinic EHR assessment and readiness (CCCEAR) instrument - Laila Choirunnah; Savitri Citra Budi; Wahyu Ratna Intanida (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Regulatory demands to implement electronic medical records in all health services, including primary care facilities, are mandatory. All primary care facilities are immediately prepared for these conditions. This article aims to assess the readiness of implementing electronic medical records based on the California Community Clinic EHR Assessment and Readiness (CCCEAR) instrument. This type of qualitative research is a case study approach. Data collection techniques using observation and interviews with relevant officers. The results of the assessment of readiness to implement electronic medical records based on CCCEAR at the UPTD Puskesmas Kartasura found that three components were in range II, namely components [1] information technology infrastructure, [2] planning and policies, and [3] budget allocation. Two components are in range III, namely [1] human resources and [2] support from the government. Overall, the UPTD Puskesmas Kartasura is ready to implement electronic medical records according to the demands of existing regulations. Approaches to related human resources and the government are needed for smooth implementation.Abstrak: Tuntutan regulasi untuk mengimplementasi rekam medis elektronik di semua layanan kesehatan, termasuk fasilitas layanan primer menjadi kewajiban yang harus dijalankan. Semua fasilitas layanan primer segera bersiap untuk kondisi tersebut. Artikel ini bertujuan untuk melakukan penilaian kesiapan implementasi rekam medis elektronik berdasarkan instrumen California Community Clinic EHR Assessment and Readiness (CCCEAR). Jenis penelitian kualitatif pendekatan studi kasus. Teknik pengambilan data menggunakan observasi dan wawancara kepada petugas terkait. Hasil penilaian kesiapan implementasi rekam medis elektronik berdasarkan CCCEAR di UPTD Puskesmas Kartasura didapatkan tiga komponen berada pada ranget II, yaitu komponen [1] infrastruktur teknologi informasi, [2] perencanaan dan kebijakan, dan [3] alokasi anggaran. Terdapat dua komponen yang berada pada range III, yaitu [1] sumber daya manusia dan [2] dukungan dari pemerintah. Secara keseluruhan UPTD Puskesmas Kartasura telah cukup siap untuk implementasi rekam medis elektronik sesuai tuntutan regulasi yang ada. Perlu upaya pendekatan pada sumber daya manusia terkait dan pemerintah untuk kelancaran implementasi.